Art platforms and cultural production on the internet - Goriunova, Olga, 1977- (New York : Routledge, 2012)
'In this book, Goriunova offers a critical analysis of the processes that produce digital culture. Digital cultures thrive on creativity, developing new forces of organization to overcome repetition and reach brilliance. In order to understand the processes that produce culture, the author introduces the concept of the art platform. An art platform is a specific configuration of creative passions, codes, events, individuals and works that are propelled by cultural currents and maintained through digitally native means. Art platforms can occur in numerous contexts bringing about genuinely new cultural production, that, given enough force, come together to sustain an open mechanism while negotiating social, technical and political modes of power.Amateur and folklore work, aesthetic forms of organization and geeky publics, creativity, freedom, and humour are reinterpreted in the theoretical apparatus offered in this book and tested through case studies derived globally. Software art, digital forms of literature, 8-bit music, 3D art forms, pro-surfers, and networks of geeks are test beds for enquiry into what brings and holds art platforms together. Goriunova provides new means of understanding the development of cultural forms on the Internet, placing the phenomena of participatory and social networks in a conceptual and historical perspective, and offering powerful tools for researching cultural phenomena overlooked by other approaches. This book an invaluable resource for scholars of digital media and cultural studies, and a readership involved in every kind of network culture.'--
Includes bibliographical references (p. [139]-146) and index.
Keywords: Art and the Internet; Arts and society; Internet -- Social aspects; Technology and the arts